EUROPEAN TYPES OF COTHILIA IN THE COLLECTIONOF THE SRI GAREEV BOTANICAL GARDEN OF NAS KR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article briefly provides information about European types of cotoneastergrowing in the Botanical Garden. E.Z. Gareeva NAS KR. Their decorative qualities and place oftheir growth are given.
Keywords: cotoneaster, shrub, leaves, flowering, fruits, drought resistance, winter hardiness.